Using remote peers' influence to promote healthy food choices among preschoolers - Kim, Elizabeth B. (2020)
Prior studies have demonstrated that social norms or cues of others' eating behaviors serve as powerful guides for one's own eating behaviors. Yet it remains underexplored whether young children are susceptible to social pressure by remote peers when faced with a conflict between what they prefer and the healthy choices of a group majority. Here we examined whether preschool-aged children conformed to healthy food choices of remote peers. Following a modified Asch conformity paradigm, the present study used videos of remote confederates' food preferences to test whether 89 3- to 6-year-old Singaporean preschoolers conformed to remote peers' healthy food choices (fruits and vegetables). Participants were asked to make a series of food choices when faced with two food options (healthy, unhealthy), both independently and after having viewed remote peers make healthy food choices (fruits, vegetables). Results showed a significant level of conformity, such that participants altered their initially unhealthy food choices to match the healthy choices of remote peers for 29% of trials. Age and BMI z-scores were also associated with rates of food choice conformity. The finding that young children may conform to food-related behaviors of remote peers offers the potential promise of interventions involving remote peers in promoting healthier dietary choices of young children.